Hybrider le climat et les luttes - Berthier, Aurélien; Mourin, Barbara (Agir par la culture, 2018)
Le concept d’intersectionnalité définit les points de rencontre entre des luttes contre les dominations liées à la classe sociale, à la racisation ou au genre. Il a permis réflexions et nouveaux champs de bataille féconds. Activistes et intellectuel·les proposent de continuer à multiplier les hybridations entre ces combats sociaux, culturels et politiques avec les luttes environnementales et climatiques. Prenant... View Article
Keywords: approches et analyses; capitalisme; environnement; intersectionnalité; justice sociale; militance; patriarcat; projet charge mentale; ressource en ligne; systèmes d'oppressions; thématiques; écoféminisme

The Black feminist spatial imagination and an intersectional environmental justice - Ducre, Kishi Animashaun (Environmental Sociology, 2018)
Starting with seminal work from Katherine McKittrick and Katherine McKittrick and the late Clyde Woods, this paper compares and contrasts articulations of justice as espoused by Black feminism, ecofeminism, and the movement for environmental justice. The utilization of an intersectional genealogical approach allows for examination of the ways in which these movements might serve as the ideological bases for a Black feminist spatial imagination and an intersectional environmental justice. A Black feminist spatial imagination is an orientation that accounts for the merger of frames around race, gender, and ecology; it serves as a unique departure from conventional Black feminist analysis by its particular attention to the construct of space in Black feminist epistemology. Analysis reveals that manifestos engage similar strategies around boundedness, an identification among a collective identity and the subject of reproductive justice and liberation as wresting control and self-determination of physical bodies. The final task is an outline of essential tenets for a singular notion of justice of a Black feminist spatial imagination which incorporates the spirit of all of three manifestos and expands current environmental justice discourse to include those ‘who know no one knows’ while highlighting Black women’s agency in environmentally degraded environments. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: afro-féminisme; amériques; approches et analyses; corps; environnement; féminismes noirs; intersectionnalité; justice environnementale; justice reproductive; projet charge mentale; régions géographiques; thématiques; écoféminisme; états-unis

Climate change, colonialism, and women’s well-being in Canada: What is to be done? - Williams, Lewis (Canadian Journal of Public Health, 2018)
The impacts of accelerating climate change across Canada are unequally distributed between populations and regions. Emerging evidence shows climate change and resultant policies to be worsening gendered social and economic inequities between women and men, with women’s participation largely absent in climate change research and decision-making. These dynamics are resulting in negative impacts for women’s well-being, with Indigenous and historically marginalized women at increased risk of experiencing health inequities as a result of climate change. To date, public health discourse has largely failed to incorporate gender as a key determinant of health in discussions of climate change impacts on populations. Paralleling this lack of development, the entangled relationship between climate and colonialism tends to be subsumed under the term “Aboriginality” within health determinants discourse. This commentary on gender and climate change in Canada is framed within a radical intersectional approach as an alternative course of public health analysis and action aimed at addressing resulting health and power inequities. Following an overview of evidence regarding the gendered impacts of climate change on women’s work, roles, agency, and well-being, several possible public health action areas on climate change and gender are highlighted as necessary components for resilient communities capable of meeting contemporary challenges.
Keywords: amériques; approches et analyses; canada; changements climatiques; environnement; intersectionnalité; invisibilisation des femmes autochtones; projet charge mentale; régions géographiques; santé; santé des femmes*; sexisme; système colonial; systèmes d'oppressions; thématiques